Zinc pyrithione activates the volume-regulated anion channel through an antioxidant-sensitive mechanism - Figueroa, Eric E. (Am J Physiol Cell Physiol, 2021)
Leucine-rich repeat-containing 8 (LRRC8) volume-regulated anion channels (VRACs) play important physiological roles in diverse cell types and may represent therapeutic targets for various diseases. To date, however, the pharmacological tools for evaluating the druggability of VRACs have been limited to inhibitors, as no activators of the channel have been reported. We therefore performed a fluorescence-based high-throughput screening (HTS) of 1,184 Food and Drug Administration-approved drugs for compounds that increase VRAC activity. The most potent VRAC potentiator identified was zinc pyrithione (ZPT), which is used commercially as an antifouling agent and for treating dandruff and other skin disorders. In intracellular Yellow Fluorescent Protein YFP(F46L/H148Q/I152L)-quenching assays, ZPT potentiates the rate and extent of swelling-induced iodide influx dose dependently with a half-maximal effective concentration (EC(50)) of 5.7 µM. Whole cell voltage-clamp experiments revealed that coapplication of hypotonic solution and 30 µM ZPT to human embryonic kidney 293 or human colorectal carcinoma 116 cells increases the rate of swelling-induced VRAC activation by approximately 10-fold. ZPT potentiates swelling-induced VRAC currents after currents have reached a steady state and activates currents in the absence of cell swelling. Neither ZnCl(2) nor free pyrithione activated VRAC; however, treating cells with a mixture of ZnCl(2) and pyrithione led to robust channel activation. Finally, the effects of ZPT on VRAC were inhibited by reactive oxygen species (ROS) scavenger N-acetylcysteine (NAC) and NAD(P)H oxidase inhibitor diphenyleneiodonium chloride, suggesting the mechanism of action involves ROS generation. The discovery of ZPT as a potentiator/activator of VRAC demonstrates the utility of HTS for identifying small-molecule modulators of VRAC and adds to a growing repertoire of pharmacological tool compounds for probing the molecular physiology and regulation of this important channel.